(untitled) (Journal of Economic Research & Business Administration, 2016)
Monetary policy are the elements of single public economic policy that includes social, structural and outwardlyeconomic politics also. Thus, strategic aim of public moneyandcredit policy as major directions of eco nomic politics of the state there is providing of effective employment, sta bility of prices, strong, longterm economic growth. For the estimation of efficiency of monetary policy indexes must be examined in a dynamics reflecting positive forward realization of monetary policy and growth of her role in an economy. Forming of effective monetary policy supposes a priority entity of monetary policy selection from those that exist: sug gestion of money or demand on money, volume and structure of amount of money, coefficients of the money (bank) making of animated cartoon, course of national monetary item volume of credits that get to the partici pants of turnover, including, to the bank sector, volume and structure of money earnings and charges of participants of turnover.